Identification of differentially expressed transcripts for trunk formation in sago palm using annealing control primer GeneFishing technique - Hasnain, Hussain; Edward-Atit, Anastasia Shera; Norzainizul, Julaihi; Rina, Tommy; Mehvish, Nisar; Nurhazlina, Hamdan; Hiroshi, Ehara (Open Science Publishers LL, 2022)
In the state of Sarawak, Malaysia’s vast peatland cultivated with sago palm (Metroxylon sagu), a considerable amount of cases involving stunted, nondeveloped trunk of sago palms was observed. Molecular-level understanding of the mechanism or pathway involved in the trunking (T) process leading to storage starch accumulation in the trunk of the sago palm is yet to be fully understood. A Polymerase Chain Reaction-based differential display analysis using Annealing Control Primer based GeneFishing technique on leaf samples of normal T compared to the nontrunking (NT) palm showed distinct differentially expressed transcripts pattern with differences in intensity between 35% and 123%. The translated sequence identified functions that are grouped under energy metabolism, nutrient regulation, biosynthetic reactions, defense mechanism, and stress tolerance. Transcripts from T showed higher expression of redox-regulating functions, while NT samples had proteins actively involved in the respiratory chain and chloroplast regulation. In nutrient regulation, the T sample showed higher transcript levels of nitrogen utilization and regulation of phosphate and cobalt, whereas NT showed activities of nitrogen uptake and regulation of calcium, magnesium, and zinc. This study identified different levels of transcripts in two physiologically different sago palms, and the formation and the development of the trunk are induced by these enzymes.